Reconfigurable Soft Robots by Building Blocks. Issue 33 (3rd October 2022) - Atia, Mohamed G. B.; Mohammad, Abdelkhalick; Gameros, Andres; Axinte, Dragos; Wright, Iain
Abstract: Soft robots are of increasing interest as they can cope with challenges that are poorly addressed by conventional rigid‐body robots (e.g., limited flexibility). However, due to their flexible nature, the soft robots can be particularly prone to exploit modular designs for enhancing their reconfigurability, that is, a concept which, to date, has not been explored. Therefore, this paper presents a design of soft building blocks that can be disassembled and reconfigured to build different modular configurations of soft robots such as robotic fingers and continuum robots. First, a numerical model is developed for the constitutive building block allowing to understand their behavior versus design parameters, then a shape optimization algorithm is developed to permit the construction of different types of soft robots based on these soft building blocks. To validate the approach, 2D and 3D case studies of bio‐inspired designs are demonstrated: first, soft fingers are introduced as a case study for grasping complex and delicate objects. Second, an elephant trunk is used for grasping a flower. Third, a walking legged robot. These case studies prove that the proposed modular building approach makes it easier to build and reconfigure different types of soft robots with multiple complex shapes. Abstract : This paper presents the design of soft building blocks that can be assembled and reconfigured to build different modular configurations of soft robots such as robotic fingers and continuum robots. To validate this approach, three case studies of bio‐inspired designs are demonstrated (2D soft fingers, legged robot, and a 3D robotic elephant trunk).